Investigating the impact of COVID-19 on patients with cancer from areas of conflict within the MENA region treated at King Hussein Cancer Center - Al-Hussaini, Maysa; Al-Ani, Abdallah; Hammouri, Muhammad; Al-Huneidy, Leen; Mansour, Asem (Frontiers in Oncology, 2023)
Background: There is a paucity of evidence regarding the impact of COVID-19 on cancer care among refugees or patients from areas of conflict. Cancer care for these populations remains fragmented due to resource scarcity and limited infrastructure. Aims: To explore the effect of COVID-19 on cancer care among patients from areas of conflict treated at KHCC. Methodology: We performed a retrospective chart review of all patients from areas of conflict, treated at KHCC from 2018 to 2021. Patients’ demographics and clinical characteristics are presented in the form of descriptive statistics. Interrupted Time Series (ITS) analysis was utilized to investigate the impact of COVID-19 on the number of admissions throughout the study’s period. Results: A total of 3317 patients from areas of conflict were enrolled in the study. Among these, 1546 were males (46.6%) while 1771 (53.4%) were female. Libyans (34.6%), Palestinians (24.8%), Iraqis (24.5%), Syrians (15.3%), and Sudanese patients (0.9%) constituted our study sample. ITS analysis demonstrated that the start of the COVID-19 lockdown significantly decreased admissions by 44.0% (p = 0.020), while the end of the COVID-19 restriction significantly improved admissions by 43.0% (p = 0.023). Among those with available SEER stages, more than a quarter of patients had distant metastasis (n = 935, 28.2%) irrespective of age and biological sex. Advanced presentations during 2020 had around approximately a 16% and 6% increase compared with 2018 and 2019, respectively. Breast cancer (21.4%), hematolymphoid cancers (18.1%), and cancers of the digestive system (16.5%) were the most common cancers among our cohort. Conclusion: Restrictions associated with COVID-19 had a significant effect on the number of admissions of patients from areas of conflict. In the long term, this effect may impact the survival outcomes of affected patients.